2009
DOI: 10.1002/jsfa.3675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humic acid on fermentation and ciliate protozoan population in rumen fluid of sheep in vitro

Abstract: BACKGROUND: Humic acid (HA) as a product of decomposition of animal and plant tissue is used in animal production as a feed supplement, antimicrobial product and growth stimulator. The objective of the present in vitro study was to investigate the effects of dietary humic acid as a commercial Humacid 60 Basic (H60B) feed additive preparation on rumen fermentation and the ciliate protozoan population in the rumen fluid of sheep using a high fibre (HF) and high concentrate (HC) diet in batch cultures and artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
2
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 40 publications
6
19
2
9
Order By: Relevance
“…Though the lack of effects of HA on whole digestibility of nutrients was not expected. Váradyová et al (2009) reported similar nutrients digestibility in in vitro batch cultures supplemented Table 2; SEM -means standard error;…”
Section: Discussionmentioning
confidence: 73%
“…Though the lack of effects of HA on whole digestibility of nutrients was not expected. Váradyová et al (2009) reported similar nutrients digestibility in in vitro batch cultures supplemented Table 2; SEM -means standard error;…”
Section: Discussionmentioning
confidence: 73%
“…Zależą one od zbilansowania dawki pokarmowej, a także od wzbogacenia jej w naturalne dodatki paszowe, takie jak: probiotyki, prebiotyki oraz związki humusowe (5,11). W nielicznych badaniach dotyczących wpływu kwasów huminowych na procesy trawienne w żwaczu stwierdzono zmniejszenie liczebności pierwotniaków i wzrost syntezy białka bakteryjnego oraz zmniejszenie stężenia lotnych kwasów tłuszczowych (3,11). Wykorzystanie składników odżywczych przez mikroorganizmy żwacza zależy od aktywności ich enzymów, dlatego poszukuje się takich dodatków paszowych, które wpłyną na procesy trawienne w żwaczu, a w konsekwencji polepszą jakość produktów końcowych -mięsa i mleka.…”
Section: Praca Oryginalnaunclassified
“…Sığırlarda yapı-lan çalışmalarda 15,16,26 mevcut çalışmamızı destekler şekilde humik asitlerin rumen NH 3 -N'nu değiştirmediği bildirilirken, başka bir çalışmada 25 ise humik asitlerin lif içeriği ve enerji içeriği yüksek rasyonlarla beslenen koyunlarda NH 3 -N konsantrasyonunu azalttığını bildirilmişlerdir. Araş-tırıcılar bu durumu rumende bulunan hazır enerji kaynağı nedeniyle amino asitlerin mikroorganizmalarca enerji kaynağı olarak kullanılmayıp daha çok mikrobiyal protein sentezinde kullanılması böylece rumen NH 3 -N'nun azalmasıyla açıklamışlardır.…”
Section: Tartişma Ve Sonuçunclassified
“…Varadyova ve ark. 25 ise yüksek dozda humik asit ilave ettikleri in vitro çalışmada humik asitlerin rumende propiyonat düzeyini azalttığını tespit etmişlerdir. Ayrıca bütirat düzeyinde artış sağladığını ve asetat düzeyinde ise herhangi bir değişiklik meydana getirmediğini bildirilmişlerdir 25 .…”
Section: Tartişma Ve Sonuçunclassified
See 1 more Smart Citation